Iowa RBA, November 1-3, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Three emails of Iowa RBA updates for November 1-3, 1999. Highlights of the updates include sightings of a Black-headed Gull, a Surf Scoter, Pacific Loon, and a Black Scoter. Epson - sheet feed/flatbed